Structural change in the Chicago region and the impact on emission inventories in a continuous-time modeling approach - Kieran Donaghy; Clifford R. Wymer; Geoffrey J. D. Hewings; Soo Jung Ha (Journal of Economic Structures, 2017)
Motivated by both the need to model recent structural economic changes and the need to understand better the nature of environmental-economic interactions, this paper introduces a continuous-time regional econometric input-output model for the Chicago economy that can be used to analyze, at disaggregated sectoral and temporal levels, the economic and environmental implications of changes exogenous to the economy. The model's solution yields estimates of emission inventories, which may be used to analyze environmental implications of various economic changes and policy restrictions. This model is the first integrated economic-environmental model of which we are aware that has been formulated and estimated in continuous time for the regional economy of a metropolitan area. We believe that the model's formulation will enable it to enjoy greater compatibility with natural science-based models, which share such a formulation and flexibility in projecting future emissions corresponding to alternative future economic scenarios and in evaluating emissions policies relevant to such scenarios.
Keywords: 330